Pemanfaatan Kotoran Sapi untuk Pertanian Terpadu Berkelanjutan di Desa Batang Tajongkek, Pariaman Selatan, Kota Pariaman - Delvi Yanti; Aninda Tifani Puari; Nika Rahma Yanti (Warta Pengabdian Andalas, 2022)
Indonesia is recently facing the fertilizer issue as the shortage supply of subsidized fertilizers is aligned with the increasing price of non-subsidized ones. So, it eventually resulted in the unstable price of agricultural commodities. The issue has been becoming an obstacle for farmers practising agricultural cultivation, particularly those in Batang Tajongkek Village, Pariaman, West Sumatra Province. It needs to develop its potential for natural resources to make organic fertilizer from cow manure. Furthermore, the solution supports the government program on establishing integrated agriculture. Two activities were conducted to empower the area's potentials, which were counselling and composting demos, respectively. The aim was to ensure knowledge transfer to the farmers regarding the technology and critical method of cow manure composting. During the counselling, the farmers were facilitated to discuss the related issue of sustainable integrated agriculture, organic farming, and the making process of compost. Meanwhile, the process of composting from cow manure was also shown during the demo. Furthermore, the farmer was facilitated to analyze the content of produced compost, which was mainly focused on the content of nitrogen (N), phosphorous (P), and potassium (K). The activities have empowered the people in the area to self-produce cow manure compost as an organic fertilizer. The analysis of the produced compost showed that the compost has yet to fulfil the national standard of solid fertilizer (SNI 7763:2018) regarding the content of macronutrients (N + P2O5 + K2O). However, the pH of produced compost has met the national standard. The pH was 7.27, which ranges from 4-9. For the compost to be utilized by the community, it is necessary to mix other materials in its manufacture so that the resulting compost complies with SNI.